Twenty years of experience of joint dry forest management in Burkina Faso - Sawadogo, L.; Tiveau, D. (Stellenbosch University, 2011)
A series of projects In Burkina Faso, West Africa, started in the 1980s led to the establishment of a system of joint forest management that should be sustainable, produce wood fuel to the nation’s capital and allow local people to engage and benefit from management of their forests. The model tested in the Nazinon state forest is the pioneer that has inspired management models throughout the country and outside its borders. Harvesting started in 1988 and the first 20-year rotation period has now come to an end. This study evaluates this management system. It assesses the current state of the resource (biodiversity and production) and tries to project future impacts of the current model. The study also provides background material for the national evaluation of the plan. The Nazinon forest management area was assessed with a sampling ratio of 0.30%. It has a functional administration and organisation of producer groups but several practises go against the management plan, such as large numbers of livestock graze in the forest and most of the land burns annually. Legal wood harvesting concentrates on six species but illegal wood harvesting is also common. The reason for and consequences of such practises are discussed. More emphasis on non-timber forest products is recommended for the revised management plan. There is also a need for better archiving systems for various types of documents, empowerment of producer groups, review of the management policies, better follow-up of regeneration and better criteria for selecting what tree individuals can be legally cut.